The image and the witness : trauma, memory and visual culture - Guerin, Frances; Hallas, Roger (London : Wallflower, 2007)
- Portraits of presence : excavating traumatic identity in contemporary Catalan testimonies / Camila Loew##- Sound, image and the corporeal implication of witnessing in Derek Jarman's Blue / Roger Hallas##- Symbolic bodies, real pain : post-Soviet history, Boris Mikhailov and the impasse of documentary photography / Matthias Christen##- Re-collecting the collective : mediatised memory and the South African Truth and Reconciliation Commission / Stephanie Marlin-Curiel##- Since we forgot : remembrance and recognition of the Armenian genocide in virtual archives / Leshu Torchin##- False witness : combat entertainment and citizen training in the United States / Karen J. Hall##- The grey space between : Gerhard Richter's 18. Oktober 1977 / Frances Guerin##- A game that must be lost : Chris Marker replays Alain Resnais' Hiroshima mon amour / Jonathan Kear##- The domestic vision of Vietnam home movies / Guy Westwell##- Constructing the image of postmemory / Tina Wasserman##- Haunting absences : witnessing loss in Doris Salcedo's Atrabilarios and beyond / Edlie L. Wong##- Picturing ruinscapes : the aerial photograph as image of historical trauma / Davide Deriu##- Not looking at lynching photographs / James Polchin##- Here and then : the act of remembering in Richard Dindo's documentaries / Marcy Goldberg##- Megatronic memories : Errol Morris and the politics of witnessing / Devin Orgeron and Marsha Orgeron.
boek